Strategy for Cultivating Independence Through the Essential Method of Habitual Behavior in Early Childhood - Anissa Oktaviani; Azi Matur Rahmi (Suluah Pasaman, 2026)
This study aims to examine the strategy of cultivating independence in children aged 5–6 years through the Essential Behavioral Habituation Method at Rainbow Kids Kindergarten, Cibitung District, Bekasi Regency, West Java. The novelty of this study lies in the use of the Essential Behavioral Habituation Method concept which emphasizes the internalization of the value of independence through consistent, structured, and continuous habituation in various children's daily activities. The study used a descriptive qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the cultivation of independence was carried out through four forms of habituation, namely routine habituation, spontaneous habituation, role models, and programmed habituation. The implementation of this method encourages the development of children's abilities in self-care, obeying rules, making simple decisions, and being responsible for daily tasks and activities. Supporting factors for success include teacher consistency and a conducive school environment, while the main obstacles come from differences in family parenting patterns and a lack of continuity in habituation at home. Research findings show that the Essential Behavioral Habituation Method is effective as a strategy to strengthen the independence of early childhood through a gradual and continuous process of forming behavior